World experience in identifying metacognitive competencies of a teacher in the course of professional development and work with gifted children - P. V. Smirnova; V. P. Peskov (Acta Biomedica Scientifica, 2022)
Today, there are significant requirements for the professional competencies of a teacher, among which a special place is occupied by competencies that determine the effectiveness of work with different categories of students. The article presents the results of a theoretical comparison of conceptual approaches to the identification and development of professional competencies of future teachers. The metacognitive competencies underlying self-learning are analyzed. The role of special work within the framework of individual educational courses, trainings and practices in higher education, aimed at developing metacognitive strategies and competencies of future teachers, is substantiated. The article proposes a support structure for the components of metacognitive competence (metacognitive knowledge, declarative knowledge, metacognitive strategies). After analyzing the concept map and comparing various models of identification and development of metacognitive competence, the authors single out research, managerial and communicative competences in its structure.An analysis of domestic research highlights the role of managing competencies for  working with a gifted child and shows that a future teacher must constantly develop regulatory and personal qualities in himself and in a gifted student. When working with a gifted student, a teacher needs metacognitive competence, which is formed in the process of asking questions to oneself, in attempts to try other strategies for solving pedagogical situations. The teacher is required not only to be able to teach, but also to constantly learn himself in order to be able to solve non-trivial situations together with students.It is shown how the relationship between a teacher and students affects psychological health, well-being, psychological burnout, the quality of professional activity, the ability to work with a gifted person. The conclusion is made about how approaches to the professional training of specialists in the educational sphere should change in order to provide the opportunity to work with the category of gifted children.